Assessing the feasibility of a web‐based outcome measurement system in child and adolescent mental health services – myHealthE a randomised controlled feasibility pilot study. Issue 1 (9th June 2022) - Morris, Anna C.; Ibrahim, Zina; Heslin, Margaret; Moghraby, Omer S.; Stringaris, Argyris; Grant, Ian M.; Zalewski, Lukasz; Pritchard, Megan; Stewart, Robert; Hotopf, Matthew; Pickles, Andrew; Dobson, Richard J. B.; et al.
Abstract : Background: Interest in internet‐based patient reported outcome measure (PROM) collection is increasing. The NHS myHealthE (MHE) web‐based monitoring system was developed to address the limitations of paper‐based PROM completion. MHE provides a simple and secure way for families accessing Child and Adolescent Mental Health Services to report clinical information and track their child's progress. This study aimed to assess whether MHE improves the completion of the Strengths and Difficulties Questionnaire (SDQ) compared with paper collection. Secondary objectives were to explore caregiver satisfaction and application acceptability. Methods: A 12‐week single‐blinded randomised controlled feasibility pilot trial of MHE was conducted with 196 families accessing neurodevelopmental services in south London to examine whether electronic questionnaires are completed more readily than paper‐based questionnaires over a 3‐month period. Follow up process evaluation phone calls with a subset ( n = 8) of caregivers explored system satisfaction and usability. Results: MHE group assignment was significantly associated with an increased probability of completing an SDQ‐P in the study period (adjusted hazard ratio (HR) 12.1, 95% CI 4.7–31.0; p = <.001). Of those caregivers' who received the MHE invitation ( n = 68) 69.1% completed an SDQ using the platform compared to 8.8% in the control group ( n = 68). The system was well received by caregivers, who cited numerous benefits of using MHE, for example, real‐time feedback and ease of completion. Conclusions: MHE holds promise for improving PROM completion rates. Research is needed to refine MHE, evaluate large‐scale MHE implementation, cost effectiveness and explore factors associated with differences in electronic questionnaire uptake.